(untitled) (Global Journal of Science Frontier Research, 2022)
We developed a new three-parameter extended inverse Lomax distribution called the Lehmann Type-2 inverse Lomax distribution. We demonstrated its superiority over the inverse Lomax distribution through various theoretical and practical approaches. The derived properties include the quantiles, moments, incomplete moments, entropy (Renyi and Tsallis), and order statistics. Finally, we consider two life-time data sets to show how the practitioner can take advantage of the new Type-2 inverse Lomax model. .